Multiracialism and Meritocracy in Singapore: Conventional Wisdom Reconsidered - TAN, Eugene K. B. (Institutional Knowledge at Singapore Management University, 2004)
Singapore has become widely known as a successful experiment in multiracialism and meritocracy. The apparently successful management of ethnic relations in Singapore has been attributed to the ostensibly race-blind vision of its leaders. In his talk, Eugene Tan will challenge this orthodox interpretation. He will argue instead that Singapore's rulers have not only been acutely aware of ethnicity and its importance. They have intentionally mobilized race, culture, and language as key political resources to ensure that Singapore remains a sophisticated, authoritarian, developmental state.